Review of Active Learning Methods in Pharmacology Course - Sadaat, Syed Sher Shah (Journal of Natural Sciences – Kabul University, 2022)
Pharmacology is one of the applied science subjects taught in Veterinary Medicine, Human Medicine, Dentistry, and Pharmacy Faculties. The subject enables students to understand drugs, their effects, the fate of drugs in the body, and their safe use in the treatment process. The learning process in higher education in our country has traditionally been passive, relying on lecturing methods that focus mainly on theoretical knowledge. This method prioritizes the teacher’s access to learning rather than student engagement. Given that the pharmacology course encompasses various branches, an active learning method is essential. Active learning, which involves student participation, is necessary to enhance the learning experience. Some of these methods include Case-Based Learning (CBL), Problem-Based Learning (PBL), brainstorming, discussions, role-playing, student participation, and PowerPoint presentations. In conclusion, transferring knowledge through active learning is more effective.